Evidence Project Final Report: Evaluating the productivity, environmental sustainability and wider impacts of agroecological compared to conventional farming systems - Burgess, Paul J.; Staley, Joanna T.; Hurley, Paul D.; Rose, David Christian; Redhead, John R.; McCracken, Morag E.; Girkin, Nicholas T.; Deeks, Lynda K.; Harris, Jim A. (DEFRA, 2023)
Agriculture is a major cause of greenhouse gas (GHG) emissions, biodiversity loss, and pollution. Agroecological and regenerative farming have been advocated as alternative approaches that may have fewer negative (or even net positive) environmental impacts than conventional agriculture at farm- and landscape-scales, leading to considerable interest in these approaches (Newton et al. 2020; Bohan et al. 2022; Prost et al. 2023). This report forms the third part of a Defra-funded project Evaluating the productivity, environmental sustainability and wider impacts of agroecological and regenerative farming systems compared to conventional systems. The first part of this project was a rapid evidence review of agroecological and regenerative farming systems and their impacts (Burgess et al. 2023), and the second reported interview findings to examine farmer and stakeholder perspectives on barriers and enablers in agroecological and regenerative farming (Hurley et al. 2023). This third part of the project characterised the current research capability in agroecology and regenerative farming, and explored the potential role of a new ‘living lab’ trial network.
Report for DEFRA